2022
DOI: 10.3904/kjim.2021.515
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular filtration rate as a kidney outcome of diabetic kidney disease: a focus on new antidiabetic drugs

Abstract: Diabetes has reached epidemic proportions, both in Korea and worldwide and is associated with an increased risk of chronic kidney disease and kidney failure (KF). The natural course of kidney function among people with diabetes (especially type 2 diabetes) may be complex in real-world situations. Strong evidence from observational data and clinical trials has demonstrated a consistent association between decreased estimated glomerular filtration rate (eGFR) and subsequent development of hard renal endpoints (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 120 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…In addition to their glucose-lowering effect, SGLT2 inhibitors have beneficial effects on cardiovascular and renal disease risk factors, such as weight loss and blood pressure reduction [19,20]. Indeed, cardiovascular and dedicated renal outcome trials of SGLT2 inhibitors have demonstrated that these drugs inhibit and delay the development and progression of cardiovascular and renal diseases [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their glucose-lowering effect, SGLT2 inhibitors have beneficial effects on cardiovascular and renal disease risk factors, such as weight loss and blood pressure reduction [19,20]. Indeed, cardiovascular and dedicated renal outcome trials of SGLT2 inhibitors have demonstrated that these drugs inhibit and delay the development and progression of cardiovascular and renal diseases [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic kidney disease (DKD), characterized by a gradually decreasing glomerular filtration rate (GFR) with or without albuminuria, has been considered the leading cause of chronic kidney disease (CKD) and end-stage kidney disease (ESKD) worldwide [ 1 ]. In patients with type 1 diabetes mellitus (DM) and type 2 DM (T2DM), the prevalence of DKD is 30% and 40%, respectively [ 2 ].…”
mentioning
confidence: 99%
“…In patients with type 1 diabetes mellitus (DM) and type 2 DM (T2DM), the prevalence of DKD is 30% and 40%, respectively [ 2 ]. Because DKD is highly prevalent in patients with DM, it increases the risk of CKD progression along with cardiovascular morbidity and mortality, making early detection and prediction of the prognosis for DKD important [ 1 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation